Quando incentivos partidários aumentam chances de mulheres serem eleitas: análise das eleições municipais de 2024 aos executivos municipais - Costa, Maria Eduarda Tencati da (Universidade Federal de São Carlos, 2026)
The underrepresentation of women in Brazilian politics persists as a structural democratic challenge, evidenced by the low occupation of women in municipal Executive positions. This dissertation investigates the role of political parties as gatekeepers and analyzes which party incentives increase the chances of women being recruited and elected as mayors in the 2024 elections. The research is based on the premise that the internal structure of parties and the distribution of resources are determinants in the supply of competitive candidacies. Methodologically, the study employs a quantitative approach based on data from the Superior Electoral Court (TSE), applying Binary Logistic Regression models to test the impact of variables such as the presence of women in party leadership positions (president, general secretary, and treasurer), campaign finance, ideological spectrum, and municipality size. The results indicate that, while the predictive model for electoral success has limitations due to the complexity of voter behavior, structural variables are decisive in the recruitment stage. The analysis demonstrated that the presence of female leadership in municipal party bodies triples the chances of a woman becoming a candidate, confirming the hypothesis that internal inclusion boosts political supply. Furthermore, it was observed that public funding is the primary source for female campaigns, given the barrier to accessing private resources, and that small municipalities prove to be more fertile ground for the election of female mayors. It is concluded that political parties are the central variables in maintaining or breaking the gender status quo, operating filters that limit female competitiveness even before the election begins.
Impact of party incentives on women's electoral prospects: an analysis of the 2024 brazilian mayoral elections
Keywords: Gênero e Política; Eleições Municipais 2024; Partidos Políticos; Recrutamento Político; Gender and Politics; 2024 Municipal Elections; Political Parties; Political Recruitment; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO; 5. Igualdade de Gênero